2020
DOI: 10.1002/nur.22085
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial resources contributing to resilience in Austrian young carers—A study using photo novella

Abstract: Caring for their chronically ill or disabled family members is a responsibility that may be assumed by children and adolescents ("young carers") and may affect young carers' lives in many ways. Some young carers may experience long-term adverse health effects related to their early caring responsibilities and others may demonstrate healthy adaptation. Little research applying nonretrospective designs, however, has been done from the perspective of young carers regarding the psychosocial resources that enable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…What is important to recognise here is that there is nothing unusual or exceptional about these dynamics. Indeed, this recognition mirrors the assertion made by (Matzka & Nagl-Cupal, 2020) that what allows YCs and their families to deal with the challenges they face are "basic, yet effective, human adaptational systems that may be cultivated and promoted with systemic support" (p.9). The fact that these dynamics have been identified in this study as being key for facilitating change for YCs, implies that they are not being sufficiently enabled for these young people within other environments such as at home or in school.…”
Section: Key Dynamicsmentioning
confidence: 62%
See 2 more Smart Citations
“…What is important to recognise here is that there is nothing unusual or exceptional about these dynamics. Indeed, this recognition mirrors the assertion made by (Matzka & Nagl-Cupal, 2020) that what allows YCs and their families to deal with the challenges they face are "basic, yet effective, human adaptational systems that may be cultivated and promoted with systemic support" (p.9). The fact that these dynamics have been identified in this study as being key for facilitating change for YCs, implies that they are not being sufficiently enabled for these young people within other environments such as at home or in school.…”
Section: Key Dynamicsmentioning
confidence: 62%
“…personal resources and interpersonal resources). Again the project interventions in this present study support both these types of resources, for example by enabling leisure time (personal resource) and fostering meaningful friendships (interpersonal resource) including promoting cohesion within the nuclear family (Matzka & Nagl-Cupal, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, previous research showed that mothers show high levels of stress ( 1 ) and low levels of self-esteem ( 2 ). In addition, siblings may face limited access to the attention of the caregiver ( 3 , 4 ), higher levels of caregiving responsibility ( 5 ), and mature behavior ( 6 ) compared to their peers or act like a young carer ( 7 9 ). Although a system or family-centered approach is now very common in early intervention services for children with disabilities ( 10 12 ), these models focus mainly on the children with disabilities themselves and their caretakers, with only marginal attention paid to the siblings.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, caring responsibilities in the adolescent phase may have a serious impact on psychosocial adjustment and represent a challenge to life planning in relation to education, career and personal life [ 9 , 26 ]. However, self-efficacy beliefs, perceived social support, opportunities for leisure/recreation and meaningful social interactions and emotional engagement with school may act as protective factors, as they have been linked to better adjustment to the caring role, physical and psychosocial well-being and educational achievement [ 7 , 14 , 27 , 28 ]. Furthermore, resilience and a positive sense of self-identity have been suggested to promote coping with caring circumstances [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%